Current statement and safe implementation of minimally invasive surgery in the pancreas. Issue 5 (9th July 2020) - Hayashi, Hiromitsu; Baba, Hideo
Abstract: Minimally invasive pancreatic resection has become very popular in modern pancreatic surgery. Evidence of the benefits of a minimally invasive approach is accumulating thanks to prospective and randomized controlled studies. Minimally invasive surgery provides advantages to the surgeon due to the high definition of the surgical field and the freedom of fine movement of the robot, but should be considered only in selected patients and in high‐volume centers. Minimally invasive distal pancreatectomy for benign and low‐grade malignant tumors has established a secure position over open distal pancreatectomy, since it is associated with a shorter hospital stay, reduced blood loss, and equivalent complication rates. Minimally invasive distal pancreatectomy for pancreatic ductal adenocarcinoma appears to be a feasible, safe, and oncologically equivalent technique in experienced hands. On the other hand, the feasibility and safety of minimally invasive pancreaticoduodenectomy are still controversial compared with open pancreaticoduodenectomy. The choice of either technique among open, laparoscopic, and robotic approaches depends on surgeons' experience and hospital resources with a focus on patient safety. Further studies are needed to prove the perioperative and oncological advantages of minimally invasive surgery compared to open surgery in the pancreas. Here, we review the current status of minimally invasive pancreatic surgery and its safe implementation. Abstract : Safe implementation of minimally invasive pancreatic surgery and its learning curve.